Construction and transient expression of the Cap protein of porcine circovirus 3 in Nicotiana benthamiana - Tran, Thu Hoai; Ho, Thi Thuong; Nguyen, Minh Chau; Pham, Bich Ngoc; Pham, Thi Van (Vietnam Journal of Biotechnology, 2025)
Porcine circovirus (PCV) leads to severe illnesses in pigs, including postweaning multisystemic wasting syndrome (PMWS), reproductive impairments, and kidney disease syndrome. Among the four recognized genotypes (PCV1–PCV4), PCV3 has emerged as a globally distributed pathogen that includes Vietnam and represents a major economic burden to the global pig farming industry. Acting as a major immunogen, the Cap protein effectively induces protective immunity, highlighting its potential as a target antigen for subunit vaccines against PCV3. In this study, a plant expression vector carrying the gene encoding the Cap3 protein fused with the GCN4pII motif (Cap3-pII) was constructed and then introduced into Agrobacterium tumefaciens. The transformed bacteria were then infiltrated into Nicotiana benthamiana leaves. Western blot analysis confirmed the expression level of the Cap3-pII protein, with a yield of approximately 13 mg/kg of fresh leaf. These results provide a basis for further research on developing a subunit vaccine against PCV3 using transient expression technology in plants.